Oreocharis parviflora, a new species of Gesneriaceae from northwestern Yunnan, China - Lei, Cai; Huang, Hua; Dao, Zhi-Ling; Wu, Zhi-Kun (Phytotaxa, 2017)
A new species of Gesneriaceae, Oreocharis parviflora, is described and illustrated from Lanping County, northwestern Yunnan Province, China. The new species is morphologically similar to O. henryana in the shape and color of corolla, numbers of stigma, stamen and staminode characteristics, but it can be easily distinguished by the shape of leaf blade, indumentum characters of leaf blade, petiole, peduncle and pedicel.